Membrane Treatment to Improve Water Recycling in an Italian Textile District - Francesca Tuci; Michele Allocca; Donatella Fibbi; Daniele Daddi; Riccardo Gori (Membranes)
The textile district of Prato (Italy) has developed a wastewater recycling system of considerable scale. The reclaimed wastewater is characterized by high levels of hardness (32 °F on average), which precludes its direct reuse in numerous wet textile processes (e.g., textile dyeing). Consequently, these companies utilize ion exchange resins for water softening. However, the regeneration of the resins results in an increased concentration of chlorides in the reclaimed wastewater that exceeds the limit set by Italian regulations for the reuse of water for irrigation purposes. The objective of this study is to investigate the potential of membrane filtration as an alternative method for removing hardness from water. Therefore, an industrial-scale ultrafiltration-nanofiltration (UF-NF) pilot plant was installed to test the rejection of hardness from the reclaimed wastewater. The experiment employed two types of NF membranes and three permeate fluxes (27, 35, and 38 L·m−2·h−1) for testing. The results demonstrated that the system could remove hardness with efficiencies exceeding 98% under all conditions tested. The experimental findings indicate that the UF-NF system has the potential to be employed as a post-treatment step to render the reclaimed wastewater suitable for all textile finishing processes and to expand the scope for reuse.